2002
DOI: 10.1103/physreve.65.031302
|View full text |Cite
|
Sign up to set email alerts
|

Granular friction, Coulomb failure, and the fluid-solid transition for horizontally shaken granular materials

Abstract: We present the results of an extensive series of experiments, molecular dynamics simulations, and models that address horizontal shaking of a layer of granular material. The goal of this work was to better understand the transition between the "fluid" and "solid" states of granular materials. In the experiments, the material-consisting of glass spheres, smooth and rough sand-was contained in a container of rectangular cross section, and subjected to horizontal shaking of the form x=A sin(omega(t)). The base of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 24 publications
3
47
0
Order By: Relevance
“…Important non equilibrium effects of structurally disordered granular systems, beside the slow relaxation to equilibrium [12,22,23], are : bistability and hysteresis [24,25,26] as the result of a memory effect due to the internal history dependence of systems out of equilibrium and the lack of an unique metastable state [2] ; and a jerky response to the external driving force with impulselike events (local rearrangements of grains or avalanches), as the result of the exploration of local minimal energy configurations [27,28]. A related important question is whether a diverging length-scale exists on the jammed side of the transition [29].…”
Section: Introductionmentioning
confidence: 99%
“…Important non equilibrium effects of structurally disordered granular systems, beside the slow relaxation to equilibrium [12,22,23], are : bistability and hysteresis [24,25,26] as the result of a memory effect due to the internal history dependence of systems out of equilibrium and the lack of an unique metastable state [2] ; and a jerky response to the external driving force with impulselike events (local rearrangements of grains or avalanches), as the result of the exploration of local minimal energy configurations [27,28]. A related important question is whether a diverging length-scale exists on the jammed side of the transition [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent hydrodynamic model based on phase transition theory describes the granular material as a two-phase material with a "solid" (static) and a "liquid" (flowing) phase [7]. This transition, also advocated in others conditions [8,9], is important for the understanding of avalanche instability in the context of risk assessment.…”
mentioning
confidence: 99%
“…Based on detailed experiments with a bed of grains in a rectangular box, Metcalfe et al [104] concluded that convective flow in the horizontal plane can occur because of side wall shearing. Furthermore, convection can occur in the vertical plane due to the avalanching of grains that occurs in the gaps that open up near the side wall as the grains get sloshed from side to side.…”
Section: Impact Of Direction Of Vibrationmentioning
confidence: 99%